2003
DOI: 10.1016/s0002-9440(10)63544-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocytes Express Nerve Growth Factor during Liver Injury

Abstract: A key feature of recovery from liver fibrosis is hepatic stellate cell (HSC) apoptosis, which serves the dual function of removing the major source of neomatrix and tissue inhibitors of metalloproteinases thereby facilitating matrix degradation. The mechanisms regulating HSC apoptosis remain undefined but may include the interaction of nerve growth factor (NGF) with its receptor, p75, on HSC. In this study, by TaqMan polymerase chain reaction in situ hybridization and immunohistochemistry, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…Furthermore, it has recently been shown that hepatocytes express NGF during liver injury and that at the peak of this expression there is maximal HSC apoptosis. 47 This provides evidence for possible paracrine regulation in vivo.…”
Section: Growth Factors and Soluble Mediatorsmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, it has recently been shown that hepatocytes express NGF during liver injury and that at the peak of this expression there is maximal HSC apoptosis. 47 This provides evidence for possible paracrine regulation in vivo.…”
Section: Growth Factors and Soluble Mediatorsmentioning
confidence: 75%
“…100 Several studies provide indirect evidence of an antiapoptotic role for NF-κB in HSC. NGF (see above) induced apoptosis of HSC is associated with inhibition of p50/p65 DNA binding detected by electromobility shift assays as well as suppression of NF-κB transcriptional activity as determined by NF-κB reporter assays 47 This relative reduction in NF-κB binding is associated with an increase in caspase 3 activity. Similarly, curcumin induction of HSC apoptosis is also associated with inhibition of NF-κB binding as well as reduction of its trans-activating activity.…”
Section: The Role Of Nf-κb and Other Transcription Factors In Hsc Apomentioning
confidence: 96%
“…Finally, in the termination phase, TGF‐β and activin suppresses the growth of hepatocytes. Recent evidence further suggests that neurotrophins (NTs) may have a role in hepatic regeneration, because their mRNA and protein levels become elevated in association with hepatocyte proliferation induced by the administration of lead nitrate in rats (3) and after PH (4) or CCl 4 treatment in mice (5).…”
mentioning
confidence: 99%
“…NF-κB activation and subsequent upregulation of anti-apoptotic protein A1 promotes HSC survival [24]. Another study has shown that some nerve growth factors are expressed during fibrotic liver injury and may regulate the number of activated HSCs via inducing apoptosis, which is related to the increase of NF-κB activity, reduction of p50/p65 binding and decrease of NF-κB CAT reporter activities [25]. There is evidence showing that competitive antagonism of NF-κB can inhibit the inflammatory response and prevent CCL4-induced hepatic injury and fibrosis [26].…”
Section: Discussionmentioning
confidence: 99%